(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The aim of the present study meant to examine the development of Sitophilus granarius, S. oryzae and S. zeamais on Triticum spelta, T. dicoccum and T. monococcum spikelets and kernels. Absence or poor number of individuals (0-8) on T. spelta and T. dicoccum is observed for all the species. In the case of T. monococcum spikelets the mean number of emerged adults, even if inferior than that one observed on T. dicoccum kernels, ranges from 52 for S. oryzae and S. zeamais to 157 for S. granarius. In fact the kernel is not completely isolated from the outside, as glumes and inner glumes are not contiguos to the kernels. A greater number of emerged adults is observed on T. spelta kernels, except S. oryzae, where the highest number of individuals occurs on T. dicoccum spikelets. The mean number of individuals emerged from T. monococcum kernels is inferi or than T. spelta and T. dicoccum kernels. T. monococcum kernels is in fact smaller, about 2/3, than T. spelta and T. dicoccum. In laboratory at 25°C and 70 ± 5% R. H. the beginning of emergence for S. granarius started 33-38 days after egg laying while S. oryzae and S. zeamais started respectively 29-40 and 33-40 after the ovideposition. Also for these species the mean of the development period seems to be significantly shorter for T. dicoccum kernels while the longest period is observed on T. monococcum spikelets.